Evaluation of Danzhi Xiaoyao powder and amlodipine sustained-release tablets in follow-up treatment of the hypertensive crisis and the interleukin-6 gene expression - Wei, Qian; Jing, Zhang; Zhi-Ye, Hao (Cellular and Molecular Biology, 2021)
Danzhi Xiaoyao powder (DXP) is an herbal formula with eight different herbs. This herbal medicine can play multiple roles in various disease treatments through its several components. In this study, the effect of DXP was evaluated on the treatment of hypertensive patients with and without amlodipine. For this purpose, 252 patients were studied with high blood pressure. The 126 patients received DXP, and the others received DXP + amlodipine for four weeks. Besides demographic and biochemical assessments (gender, BMI, age, SBP, DBP, etc.), the expression of the interleukin-6 gene was evaluated in these two groups. The results showed that the blood pressure decreased by DPX, and there was no significant difference in control of blood pressure by DPX and DXP + amlodipine. But it did not affect interleukin-6 gene expression. Therefore, it can be concluded that this drug probably uses a different mechanism than amlodipine to control blood pressure.